Implementing advance control strategies to improve the performance of a microgrid - Rajput, Isha; Verma, Jyoti; Ahuja, Hemant (Bulletin of Electrical Engineering and Informatics, 2024)
Integration of flexible and non-dispatchable renewable energy production will influence the operation and future expansion of prevailing power systems. Because of the variations in performance responses between microgrid (MG) and regular generators, including renewable energy sources-based (RES-based) MG into the electrical system may have an influence on stability analysis. The reduction in switching frequency induced by these energy processors electronic interconnected electricity producing sources has a detrimental impact on the system’s structural analysis, potentially leading to stability issues. Power infusion from RES-based MG, on the other hand, increases damping efficiency, reducing transmission line congestion and power shortage. As a result, in light of expanded MG information, it is important to analyse more complex stability problems and regulate the production of a power grid. This study will examine the effect of RES-based MG on the structural analysis and controller of a multimachine multi-area device in various scenarios This paper defines the growth of a one-of-a-kind proportional-integral-derivative (PID-based) power system stabilizer (PSS) type2 fuzzy partial order based on a meta-heuristic hybrid technique for refining the efficiency and robustness of harmonic currents.